Synthesis of Heterocyclic Scaffolds via Prins, Oxonium-Ene and Related Cyclization Reactions - Saikia, Anil K. (Synlett, 2022)
A variety of oxygen, nitrogen and sulfur heterocyclic compounds are synthesized via one-pot multicomponent Prins, aza-Prins, thia-Prins, oxonium-ene, iminium-ene and thionium-ene cyclization reactions. The reactions proceeds with high diastereo- and regioselectivity. Importantly, C–C, C–N, C–O and C–S bonds are formed in a singsle step. These procedures are extended for the synthesis of biologically active molecules and natural products.1 Introduction2 Prins Cyclization Reactions3 Oxonium-Ene Cyclization Reactions4 Conclusion
Keywords: heterocycles; Prins; oxonium-ene; one-pot; multicomponent